KAJIAN PENENTUAN SEGMENTASI DAN KELAS AIR DI SUNGAI DOLOK SEBAGAI POTENSI MANFAAT UNTUK AIR BAKU - Awiyati, Ian Tangguh; Wahyudi, Slamet Imam; Soedarsono, Soedarsono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The Dolok River, which is located between Demak Regency and Semarang Regency,Central Java Province, is widely used by residents to meet their water needs in dailylife. However, as time goes by, pollution occurs which worsens the water quality ofthe Dolok River. One of the contributing factors is the existence of several factoriesand densely populated settlements along the Dolok River. Through this research,researchers intend to determine the division of segments of the Dolok River area,analyze the morphology of the Dolok River, determine the water class of the DolokRiver, predict the potential of water classes for raw water utilization and predict thepotential for raw water supply of Klambu Kudu. The methods used in this researchare the observational study method and the STORET method to determine waterclass. From the results of the analysis, Barang Dam as an upstream river has thecharacteristics of a Barbatu riverbed, relatively small discharge, river erosion andno flooding. Kebon Batur Dam is the middle part of the Dolok river which is atransportation area for erosion from upstream to downstream. Shipping channelsare areas where mud deposits occur, erosion often occurs and causes flooding.Based on the results of field surveys, the morphology of the Dolok River is a braidedtype which generally has relatively small discharge and high levels of sediment. TheDolok River water class calculated using the STORET method is classified as ClassB, namely moderately polluted. Based on the calculation results for determiningwater class by water quality category according to PP No.22 of 2021, the DolokRiver does not have potential as raw water or PDAM drinking water, because it isincluded in the class II category and can only be used as raw water for irrigation at0.52 m3. /sec. Apart from that, there was no potential for raw water supply fromKlambu Kudu to the Dolok River, because it has a different river basin.